The Role of the α Cell in the Pathogenesis of Diabetes: A World beyond the Mirror (2021)
Type 2 Diabetes Mellitus (T2DM) is one of the most prevalent chronic metabolic disorders, and insulin has been placed at the epicentre of its pathophysiological basis. However, the involvement of impaired alpha (α) cell function has been recognized as playing an essential role in several diseases, since hyperglucagonemia has been evidenced in both Type 1 and T2DM. This phenomenon has been attributed to intra-islet defects, like modifications in pancreatic α cell mass or dysfunction in glucagon’s secretion. Emerging evidence has shown that chronic hyperglycaemia provokes changes in the Langerhans’ islets cytoarchitecture, including α cell hyperplasia, pancreatic beta (β) cell dedifferentiation into glucagon-positive producing cells, and loss of paracrine and endocrine regulation due to β cell mass loss. Other abnormalities like α cell insulin resistance, sensor machinery dysfunction, or paradoxical ATP-sensitive potassium channels (KATP) opening have also been linked to glucagon hypersecretion. Recent clinical trials in phases 1 or 2 have shown new molecules with glucagon-antagonist properties with considerable effectiveness and acceptable safety profiles. Glucagon-like peptide-1 (GLP-1) agonists and Dipeptidyl Peptidase-4 inhibitors (DPP-4 inhibitors) have been shown to decrease glucagon secretion in T2DM, and their possible therapeutic role in T1DM means they are attractive as an insulin-adjuvant therapy.